Key adaptations of SME restaurants in Malaysia amidst the COVID-19 Pandemic - Lai, Jack Hao Bin; Zainal Abidin, Muhammad Rezza; Hasni, Muhamad Zulfikri; Ab Karim, Muhammad Shahrim; Che Ishak, Farah Adibah (Social Sciences Research Society, 2020)
SME restaurants have reported declined earnings and faced challenges to remain open during the Movement Control Order (MCO) period imposed by the Malaysian government due to the Coronavirus (COVID-19) outbreak. SME decision-makers were observed to be making changes regarding their day-to-day operations and management strategies to mitigate MCO restrictions. This paper aims to review the significant adaptations made by SME restaurants in Malaysia throughout the MCO period. Three (3) prominent areas of adaptations made by decision-makers have been identified based upon ceaseless news reports and media contents. The adaptations made commonly depict actions to (i) Nurture Creativity, (ii) Sustain Reputation, and (iii) Maintain Profitability. The outcomes of this paper provide essential survival guides for SME restauranteurs to embrace the COVID-19 outbreak. These can be helpful to related policy and decision-makers to implement the crucial traits of SME restaurants to reduce the impact on SME restaurants for the foreseeable future.